2018
DOI: 10.3892/mco.2018.1640
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and safety of the molecular targeted drugs afatinib, gefitinib and erlotinib as first-line treatments for patients with advanced EGFR mutation-positive non-small-cell lung cancer

Abstract: Epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs), including gefitinib, erlotinib and afatinib are standard first-line treatments for EGFR gene mutation-positive non-small cell lung cancer. The present study aimed to compare the cost-effectiveness of using erlotinib, afatinib or gefitinib. The safety of EGFR-TKIs was also investigated. Expected costs were calculated based on data from patients with advanced EGFR mutation-positive non-small-cell lung cancer who were treated with gefitinib,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Currently, the main treatment methods for lung cancer include surgical and non‐surgical treatment; non‐surgical treatment consists of radiotherapy, chemotherapy, and immunity and molecular targeted drugs. However, there are many defects in both individual and comprehensive treatment schemes . Therefore, new and targeted drug research is the current focus for the prevention and treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the main treatment methods for lung cancer include surgical and non‐surgical treatment; non‐surgical treatment consists of radiotherapy, chemotherapy, and immunity and molecular targeted drugs. However, there are many defects in both individual and comprehensive treatment schemes . Therefore, new and targeted drug research is the current focus for the prevention and treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many defects in both individual and comprehensive treatment schemes. [5][6][7] Therefore, new and targeted drug research is the current focus for the prevention and treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the epidermal growth factor receptor gene ( EGFR ) are the most common and actionable molecular aberrations in non‐small cell lung cancer (NSCLC) . Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) are effective in the treatment of advanced lung cancers harbouring EGFR mutations ( EGFR m), but remain expensive especially given continuous dosing for the duration that a patient benefits from these TKIs …”
Section: Introductionmentioning
confidence: 99%
“…Obviously, longer survival of patients with NSCLC definitely increases the overall healthcare costs for this category of patients. In terms of cost-effectiveness, a faceto-face comparison of three TKI treatment regimens (gefitinib, erlotinib and afatinib), gefitinib was found to be the most cost-effective TKI molecule (30). In a study by Tink et al, TKIs (erlotinib and afatinib) were found to be more cost-effective compared to cisplatin-pemetrexed treatment (31).…”
Section: Discussionmentioning
confidence: 99%